Personality traits prospectively predict verbal fluency in a lifespan sample - Sutin, Angelina R; Terracciano, Antonio; Kitner-Triolo, Melissa H; Uda, Manuela; Schlessinger, David; Zonderman, Alan B (Psychology and aging, 2011)
In a community-dwelling sample (N = 4,790; age range 14-94), we examined whether personality traits prospectively predicted performance on a verbal fluency task. Open, extraverted, and emotionally stable participants had better verbal fluency. At the facet level, dispositionally happy and self-disciplined participants retrieved more words; those prone to anxiety and depression and those who were deliberative retrieved fewer words. Education moderated the association between conscientiousness and fluency such that participants with lower education performed better on the fluency task if they were also conscientious. Age was not a moderator at the domain level, indicating that the personality-fluency associations were consistent across the life span. A disposition toward emotional vulnerability and being less open, less happy, and undisciplined may be detrimental to cognitive performance.